Upaya Pihak Sekolah Dalam Mengatasi Perilaku Bullying di SMP Negeri 23 Kerinci - Irawan, Maulina; Wijaya, Wibi; Akbar , Waza Karia (LPPM Institut Pendidikan Nusantara Global, 2025)
This study explores bullying behavior and the efforts made by the school to address bullying at SMP Negeri 23 Kerinci. The objectives of the research are: (1) to describe the forms of bullying behavior occurring at SMP Negeri 23 Kerinci, and (2) to analyze the school's strategies in addressing these behaviors. A qualitative approach was used, with a case study as the research design. The research subject is SMP Negeri 23 Kerinci, specifically in relation to its handling of bullying issues. Data were collected through interviews, observations, and documentation. The findings show that bullying at the school occurs in both verbal and physical forms. Verbal bullying includes mocking others by using their parents’ names or giving them unusual nicknames. Physical bullying involves fighting, pushing, hitting, and disturbing others while they are writing or doing schoolwork. To address bullying behavior, the school has implemented several measures. These include an anti-bullying program aimed at raising awareness and prevention, the enforcement of school rules to maintain discipline, and collaboration among school stakeholders such as teachers, staff, and parents. These efforts reflect the school's commitment to creating a safe and supportive environment for all students.